2010
DOI: 10.1038/cgt.2010.41
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tumor suppression in vitro and in vivo by co-expression of survivin-specific siRNA and wild-type p53 protein

Abstract: The development of malignant prostate cancer involves multiple genetic alterations. For example, alterations in both survivin and p53 are reported to have crucial roles in prostate cancer progression. However, little is known regarding the interrelationships between p53 and survivin in prostate cancer. Our data demonstrate that the expression of survivin is inversely correlated with that of wtp53 protein (rs=0.548) in prostate cancer and in normal prostate tissues. We have developed a therapeutic strategy, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Survivin expression inhibits cell death induced by various apoptotic stimuli in vitro and in vivo [28,38]. In the current study, we demonstrated that As 2 O 3 is a potent down-regulator of survivin expression at both the protein and mRNA levels and a potent inducer of apoptosis in WSU-CLL cells.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Survivin expression inhibits cell death induced by various apoptotic stimuli in vitro and in vivo [28,38]. In the current study, we demonstrated that As 2 O 3 is a potent down-regulator of survivin expression at both the protein and mRNA levels and a potent inducer of apoptosis in WSU-CLL cells.…”
Section: Discussionsupporting
confidence: 54%
“…Survivin over-expression and loss of p53 function occur in many cancers [2427]. Shao et al [28] suggested a correlation between the levels of p53 and survivin proteins expressed in prostate tumors. Their data suggest that p53 may be directly altered conformationally in the presence of survivin.…”
Section: Introductionmentioning
confidence: 99%
“…By a method used in our previous studies (Zhang et al, 2007), we constructed a series of expression plasmids that contain siRNA specific to mdm2 and/or the WT p53 expression element. The pcDNA3.1-p53 plasmid containing the WT p53 coding region (Pp53) was generated as described previously (Shao et al, 2010). A siRNA with the sequence of 5Ј-GACACTTATACTATGAAAG-3Ј (Genbank accession number NM002392) was selected to specifically target the fragment corresponding to nucleotides 152 to 171 of the MDM2 mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent studies have shown that combination therapies with siRNAs that target pro-oncogenic factors, and co-expressed tumor suppressor proteins comprise highly effective treatment strategies. However, development of suitable drug delivery systems is an equally important aspect of cancer therapy (Shao et al 2010; Xu et al 2009; Zhang et al 2007, 2008). In this study, we constructed a plasmid containing both Stat3-shRNA and Endostatin cDNA (pEndo-Si-Stat3), and we used attenuated Salmonella to deliver the plasmid to an orthotopic model of prostate cancer (Fu et al 1992; Hoffman 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that delivery of therapeutic plasmids expressing specific anti-tumor siRNAs (targeting Stat3, MDM2, VEGF or survivin) and tumor suppressor proteins (e.g., GRIM-19 and p53) by attenuated Salmonella significantly reduces average tumor volume and exerts synergistic anti-tumor effects that are more effective than other delivery methods (Shao et al 2010; Xu et al 2009; Zhang et al 2008, 2007). Salmonella typhimurium specifically survive in macrophages that are involved in targeting tumor tissues.…”
Section: Introductionmentioning
confidence: 99%